Keratinocytes are capable of selectively sensing low amounts of graphene-based materials: Implications for cutaneous applications. (15th April 2020) - Fusco, Laura; Pelin, Marco; Mukherjee, Sourav; Keshavan, Sandeep; Sosa, Silvio; Martín, Cristina; González, Viviana; Vázquez, Ester; Prato, Maurizio; Fadeel, Bengt; Tubaro, Aurelia
Abstract: Skin provides the first interface between body and environment, representing one of the most feasible exposure routes to graphene-based materials (GBMs). However, interactions of GBMs with the skin are poorly understood. In particular, low-concentration effects have not been investigated. Here we explored the ability of endotoxin-free, few-layer graphene (FLG) and dehydrated graphene oxide (d-GO) to initiate an inflammatory response at the cutaneous level by using human HaCaT keratinocytes. HaCaT cell exposure to low concentrations (0.01–1.0 μg/mL) of FLG or d-GO did not affect cell viability. FLG triggered the secretion of pro-inflammatory tumor necrosis factor-α (TNF-α), interleukin (IL)-1α, and IL-6, while d-GO, and to a lesser extent FLG, prompted IL-8 (CXCL8) production. However, conditioned medium from HaCaT cells exposed to FLG or d-GO had no effect on THP-1 monocyte activation. Moreover, co-culture experiments did not show any effect of FLG- or d-GO-treated HaCaT cells on THP-1 cell migration. These results suggest that while GBMs are able to initiate an inflammatory response in keratinocytes, this does not necessarily lead to activation of monocytes. The present findings are relevant for potential dermal exposures to GBMs in occupational settings as well as the use of GBMs for cutaneous applications such as in wearable sensors. Graphical abstract: Image 1